Stillbirth in an Anglophone minority of Canada - Auger, Nathalie; Daniel, Mark; Mortensen, Laust; Toa-Lou, Clarisse; Costopoulos, André (International Journal of Public Health, 2015)
Objectives We assessed trends in stillbirth over time for Francophones and Anglophones of Quebec, a large Canadian province with publically funded health care and an English-speaking minority. Methods We calculated stillbirth rates for Francophones and Anglophones, and estimated hazard ratios (HR) by decade from 1981 to 2010, adjusting for maternal characteristics. We analyzed temporal trends by gestational interval and cause of fetal death. Results Stillbirth rates decreased in Quebec during the three decades, due to improved rates in Francophones. Rates decreased for Anglophones in 1991–2000, but increased in 2001–2010 at term, during the second trimester, and for most causes of fetal death. In the 2000s, the hazard of stillbirth for Anglophones was nearly the same as the hazard for Francophones in the 1980s (HR 0.93, 95 % confidence interval 0.82, 1.05). Conclusions Stillbirth rates declined in both Francophones and Anglophones before the turn of the century, but increased thereafter for Anglophones, suggesting that linguistic inequalities in stillbirth may be emerging in Quebec. Linguistic status may be a useful marker for surveillance of inequalities in stillbirth.

Contribution of local area deprivation to cultural-linguistic inequalities in foetal growth restriction: Trends over time in a Canadian metropolitan centre - Auger, Nathalie; Park, Alison L.; Daniel, Mark (Health & Place, 2013)
This study investigated temporal trends in heterogeneity of foetal growth restriction across neighbourhood deprivation levels for two culturally distinct communities (Anglophones and Francophones) in a North American metropolitan centre. Inequalities in foetal growth restriction related to deprivation fell from 1989 to 2008 for Francophones, but initial improvements for Anglophones later reversed with a rise in poor foetal growth in the most materially disadvantaged and, unexpectedly, advantaged areas as well. Inequalities in foetal growth restriction related to neighbourhood material deprivation may be emerging in this minority Anglophone population. Potential mechanisms underlying these trends are discussed, as well as implications for perinatal health policy.

Francophone and Anglophone perinatal health: Temporal and regional inequalities in a Canadian setting, 1981-2008 - Auger, Nathalie; Park, Alison L.; Harper, Sam (Francophone and Anglophone perinatal health: Temporal and regional inequalities in a Canadian setting, 2012)
Objectives We evaluated temporal and regional inequalities in adverse birth outcomes between Anglophones and Francophones of a Canadian province. Methods Odds ratios and rate differences in preterm birth (PTB, <37 gestational weeks) and small-for-gestational-age (SGA) birth were computed for Anglophones relative to Francophones for singleton live births in Québec from 1981 to 2008 (N = 2,292,237), adjusting for maternal characteristics. Trends over time and residential region were evaluated. Results Rates of PTB and SGA birth overall were lower for Anglophones relative to Francophones, but temporal and regional trends varied by outcome. Although PTB rates increased over time, inequalities between Francophones and Anglophones were relatively stable. In contrast, inequalities in SGA birth narrowed over time as Francophone rates declined more than Anglophones. Inequalities in SGA birth favored Anglophones overall, but the gap gradually reversed in Montréal (the largest metropolitan center) to currently favor Francophones. Conclusions PTB and SGA birth rates favored Anglophones over Francophones. The linguistic gap was generally stable over time for PTB, but narrowed or reversed for SGA birth. Language may be used to capture inequalities in perinatal health in countries where different linguistic groups predominate.

Des nôtres (Volet 2): Expériences des jeunes 2ELGBTQ+ en milieu scolaire, familiale et communautaire vivant en situation linguistique minoritaire dans la province du Manitoba. - Avanthay-Strus, Jacqueline; de Moissac, Danielle; Gueye, Ndeye Rokhaya; Sandoval, Lyle-Alvien; Girard, Rhéanne; Gagné, Daniel; Costeux, Anne-Lise; Franco Morales, Freddy; Le groupe Jeunes chercheur.es; Le collectif LGBTQ* du Manitoba (Le Collectif LGBTQ du Manitoba et Université de Saint-Boniface, 2024)
Les populations ayant des identités intersectionnelles comme les jeunes 2ELGBTQ* francophones en situation linguistique minoritaire au Canada, peuvent faire face à diverses formes de discrimination dans leur vie quotidienne. Cette discrimination peut provenir de plusieurs sphères, y compris sociale, économique et institutionnelle, et elle peut entraîner des conséquences graves sur la santé mentale et physique des individus. Les études ont montré que lorsque cette discrimination est combinée au stress lié au fait d’appartenir à une minorité linguistique ou culturelle, cela peut amplifier les iniquités sociales et celles liées à la santé. Cela peut se traduire par des difficultés d’accès aux services de santé adaptés, par des taux plus élevés de dépression, d’anxiété et d’autres problèmes de santé mentale, ainsi que par des obstacles à l’inclusion sociale et économique. Une approche de recherche-action participative (RAP) a été privilégiée pour cette étude. Cette méthode efficace et inclusive a permis de faire participer étroitement les membres de la communauté au processus de recherche. Les adolescent·es et jeunes adultes francophones 2ELGBTQ* ont joué un rôle clé, non seulement en partageant leurs expériences, mais aussi en collaborant activement à la création du devis de recherche. Un devis mixte (quantitatif et qualitatif) à convergence des données a été adopté pour explorer les expériences de vie des jeunes 2ELGBTQ* d’expression française en situation linguistique minoritaire au Manitoba, dans leur milieu scolaire, familial et communautaire, ainsi qu’avec les services sociaux et de santé. Huit jeunes entre 14 et 24 ans ont participé à des entrevues progressives. Le sondage en ligne a été fait auprès de 45 jeunes de 14 à 24 ans. Six parents de jeunes 2ELGBTQ* ont participé à un entretien individuel ou à des entretiens en groupe, et quatre membres du personnel des écoles ont participé à une discussion en groupe. Trois quarts des jeunes qui ont répondu au sondage habitaient en milieu urbain. À peu près un quart d’entre eux sont des personnes autochtones, noires ou de couleur (PANDC), et trois quarts disent être bilingues (français et anglais). La grande majorité a indiqué avoir un trouble de santé mentale. Plus de la moitié a signalé une absence de réseaux de soutien en français pour les personnes 2ELGBTQ*. Un pourcentage élevé a signalé avoir des difficultés à tisser des liens ou à se faire des ami·es lors des interactions à l’école. Une difficulté à trouver des espaces surs, que ce soit en ligne ou en personne, a aussi été mentionnée. Le constat selon lequel un pourcentage élevé a signalé des difficultés à tisser des liens ou à se faire des ami·es lors des interactions à l’école indique un besoin d’amélioration des environnements éducatifs. Il est essentiel que le personnel des écoles et les autres élèves soient sensibilisés et formés pour créer des espaces surs et accueillants pour toutes les identités 2ELGBTQ* francophones. Les résultats soulignent l’urgence de mettre en place des mesures concrètes pour favoriser l’inclusion, offrir un soutien adéquat et créer des espaces sécuritaires et inclusifs pour les personnes 2ELGBTQ* francophones. Cela peut passer par des initiatives de sensibilisation, des programmes de soutien psychosocial, des ressources éducatives et des politiques visant à promouvoir la diversité et l’inclusion au sein des écoles et des communautés francophones. Les recommandations s’adressent donc aux milieux éducatifs, aux systèmes sociaux et de santé ainsi qu’à la communauté.

La littérat'ie en santé et les communautés francophones, minoritaires et ethnoculturelles - Kaszap, M.; Zanchetta, M. S. (Lire le monde : les littératies multiples et l'éducation dans les communautés francophones, 2009)

Social service accessibility in Montreal’s English-speaking disability community: A needs-based assessment - Nash, Aubrey (McGill University, 2019)
Health and social service systems can be difficult to traverse, especially in the stressful situations that often necessitate accessing them. In Quebec, these difficulties are exacerbated for English speaking or limited French-proficient persons. This thesis employs a needs-based assessment to explore how linguistic-based access barriers to health and social services affect Montreal’s English-speaking Disability community, focusing on those with intellectual and/or developmental disabilities and their caregivers/advocates. It identifies the community’s needs and proposes three key issues that result in the needs being unmet by the social service system. Specifically, the issues are (i) inaccessible information for limited French-proficient persons, as many important documents are available in only French; (ii) the primary method for bolstering language congruency between service users and providers relies on the service seeker to acquire French, which is incompatible with the lived experiences of many members of the Disability community; (iii) limited options for English services across Montreal. This thesis indicates the protection of the French language under the Charter of the French Language (1977) impacts the ability of the Act Respecting Health Services and Social Services (1991) to protect the rights of English-speaking Quebeckers to receive services in English. Through a human rights model of Disability and citizenship lens, it suggests that language laws can be understood and implemented to protect the Quebecois identity while ensuring active inclusion of otherwise marginalized communities in health and social service systems

Vers des services attirants, accessibles et pertinents pour les personnes âgées immigrantes francophones ? - Nduwimana, Mathilde; Home, A. (Reflets, 1995)
Cet article décrit et analyse les besoins et préoccupations des personnes âgées autonomes appartenant aux groupes ethniques francophones et résidant dans Ottawa-Carleton. L'objectif principal est d'explorer les raisons pour lesquelles elles utilisent peu les services de soutien communautaires pour les personnes âgées francophones. Nous avons effectué des entrevues semi-structurées auprès de quatre représentantes et de six personnes âgées des communautés ethno-culturelles francophones, et nous avons effectué une analyse de contenu par thème. Les répondantes ont souligné les besoins de contacts sociaux, d'apprentissage du français et/ou de l'anglais, d'accès aux moyens financiers adéquats et d'information sur les ressources disponibles. Des obstacles liés au contexte socio-écono-politique dans la société d'accueil entravent la satisfaction de ces besoins. La levée de certaines barrières concrètes, la modification des politiques sociales et des pratiques d'intervention faciliteraient l'accès aux services par les personnes âgées des groupes ethniques francophones et augmenteraient leurs options.

La santé sexuelle des jeunes femmes afro-francophones de Toronto - Parrot, Claire (Reflets, 2000)

Des nôtres : une analyse des besoins des personnes LGBTQ2S d’expression française du Manitoba - Prada, Kevin; de Moissac, Danielle; Gueye, Ndeye Rokhaya (Collectif LGBTQ du Manitoba et Université de Saint-Boniface, 2021)
Cette étude, menée sous l’impulsion du Collectif LGBTQ* du Manitoba, est la première à sonder les besoins de la communauté LGBTQ2S d’expression française au Manitoba (désormais la « Communauté »). L’objectif était de brosser le portrait de la situation actuelle de ses membres de 18 ans et plus quant à 1) leur profil sociodémographique et ethnoculturel; 2) leurs besoins en matière de soutiens sociaux et de soins de santé; 3) leurs perceptions de discrimination ou de stigmatisation, tant par rapport à la langue qu’à l’orientation sexuelle et/ou à l’identité de genre; et 4) leurs priorités pour l’avenir. Par l’entremise d’un sondage en ligne, la Communauté a su nous informer de ses besoins prioritaires, particulièrement en matière de santé mentale et de soutien social.

Living in a liminal space: Experiences of 2SLGBTQ + official language minority Canadians during the COVID-19 pandemic - Prada, Kevin; de Moissac, Danielle; Gueye, Ndeye Rokhaya; Hardy, Stephan; Avanthay-Strus, Jacqueline (Culture, Health & Sexuality, 2023)
The intersecting identities of those identifying with multiple minorities, such as 2SLGBTQ + and ethnolinguistic minorities, bring individuals to have unique experiences, especially concerning health and wellness. This topic is particularly poorly understood among French-speaking official language minority 2SLGBTQ + populations in Canada. Hence, this study was conducted to generate insights into their needs and experiences, through the lens of intersectionality. This quantitative community-based study, a first of its kind in Western Canada, describes the sociodemographic profile, experiences of discrimination and stigmatisation, and needs and challenges pertaining to mental health and social supports of this double minority group. Data were obtained by an online survey conducted in the Canadian province of Manitoba in June 2020. The participant sample was largely homogenous: most were under the age of 55 years, white, educated, and from urban areas. Many reported experiencing dual marginalisation, feeling unaccepted by both of their minority communities (Francophone and 2SLGBTQ+). A sense of isolation, as well as a lack of social connectedness and psychological support, were often reported. Social initiatives and mental health support within environments proactively affirming of the official language of the minority and inclusive of diverse 2SLGBTQ + identities are needed.

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Portrait de la prématurité et des naissances ayant un faible poids pour l’âge gestationnel dans les communautés linguistiques au Québec, 1989 à 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, M.; Auger, Marianne (Institut national de santé publique du Québec, 2018)

Portrait of preterm and small-for-gestational-age births by linguistic community in Québec, 1989 to 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, Marianne; Auger, Nathalie (Institut national de santé publique du Québec, 2018)